EFFECTIVENESS OF VARIOUS MEDICATIONS ON POST OPERATIVE PAIN OF VITAL TEETH AFTER ROOT CANAL THERAPY - Akula Madhavi; Umakanth kakarlapudi; Potpally Sowmya; Udaykumar M (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Postoperative pain is a common concern after root canal therapy, particularly in vital teeth, due to inflammation and periapical irritation. Despite improvements in endodontic procedures, effective pain management remains a critical aspect of patient care. Various pharmacologic agents are used to control postoperative discomfort, with differing degrees of success. Aim: To compare the effectiveness of Betamethasone, Indomethacin, and Ibuprofen in reducing postoperative pain following root canal treatment in vital teeth. Material and Methods: A randomized, double-blind, placebo-controlled clinical trial was conducted on 80 patients undergoing root canal therapy on vital teeth. Participants were randomly assigned into four groups (n = 20): Placebo, Indomethacin (25 mg), Betamethasone (0.5 mg), and Ibuprofen (400 mg). Medications were administered orally 30 minutes before the procedure. Pain levels were recorded using a Visual Analog Scale (VAS) at 6, 12, 24, and 48 hours post-treatment. Data were analyzed using SPSS version 26.0 with repeated measures ANOVA and post hoc tests. Results: All three active medications significantly reduced postoperative pain compared to placebo at all time intervals (p < 0.001). Betamethasone consistently showed the lowest mean pain scores across all time points, followed by Ibuprofen and Indomethacin. By 48 hours, moderate to severe pain (VAS ≥ 4) was absent in the Betamethasone group, while 25.00% of placebo patients continued to experience significant pain. Adverse effects were minimal and not statistically significant among groups. Conclusion: Preoperative administration of Betamethasone, Ibuprofen, and Indomethacin significantly reduced postoperative pain after root canal therapy, with Betamethasone demonstrating the highest efficacy and excellent tolerability. These findings support the use of corticosteroids, particularly Betamethasone, as an effective premedication strategy for managing post-endodontic pain.